Anti-neuroinflammatory effects of conjugated linoleic acid isomers, c9,t11 and t10,c12, on activated BV-2 microglial cells - Porcedda, Clara; Manca, Claudia; Carta, Gianfranca; Piras, Franca; Banni, Sebastiano; Sogos, Valeria; Murru, Elisabetta (Frontiers in Cellular Neuroscience, 2024)
Conjugated linoleic acid (CLA) isomers exhibit anti-inflammatory properties within the central nervous system (CNS). This study investigated the effects of CLA isomers c9,t11 and t10,c12 on fatty acid (FA) and N-acylethanolamine (NAE) profiles and their association with pro-inflammatory molecule expression in BV-2 microglia cell line, the CNS's resident immune cells responsible for maintaining neuronal activity and immune homeostasis.BV-2 cells were treated with 25 µM of c9,t11-CLA, t10,c12-CLA, or oleic acid (OA) for 24 hours, followed by lipopolysaccharide (LPS) stimulation. After treatment, the cell's FA and NAE profiles and pro-inflammatory molecule expression were analyzed.Our results demonstrated that CLA isomers mitigate LPS-induced morphological changes in BV-2 cells and reduce gene expression and protein levels of inflammatory markers. This effect was linked to an upregulation of acyl-CoA oxidase 1, a key enzyme in the anti-inflammatory peroxisomal betaoxidation pathway that efficiently metabolizes CLA isomers. Notably, t10,c12-CLA significantly suppressed stearoyl-CoA desaturase 1, impacting monounsaturated fatty acid synthesis. The NAEs profile was remarkably altered by CLA isomers, with a significant release of the antineuroinflammatory mediator docosahexaenoic acid (DHA)-derived N-acylethanolamine (DHAEA).In conclusion, our findings suggest that the anti-neuroinflammatory effects of CLA isomers are due to their unique influences on FA metabolism and the modulation of bioactive FA-derived NAEs, highlighting a potential strategy for nutritional intervention in conditions characterized by neuroinflammation.